Enhancement of Technical and Economic Indicators of Power-Generating Units of Thermal Power Plants by Eliminating Flue Gas Recirculation - Taras Kravets; Yevhen Miroshnychenko; Andrii Kapustianskyi (Energy Engineering and Control Systems)
Boiler units at Ukrainian thermal power plants need to be modernized or replaced in the short run, as this is important for the national energy security. The authors determined one of possible ways to improve the efficiency indicators of coal-fired boiler units and power generating units as a whole up to the values exceeding the design ones. This variant of improvement consists in abandoning the technology of using flue gas as drying agent in pulverized coal systems and replacing it with direct discharge of the gas flow into the boiler furnace. Numerous computations were carried out to study the change of efficiency indicators and manoeuvrability of power generating units due to the replacement of the ball mill pulverizing system using flue gases for coal drying with the scheme including ball-and-race mills that use hot air as drying agent.